“Patient Comfort Can Be Sacrificed for Patient Safety”—Perception and Practice Reported by Critical Care Nurses Toward Physical Restraints: A Qualitative Descriptive Study - Cui, Nianqi; Qiu, Ruolin; Zhang, Yuping; Jin, Jingfen (Frontiers in Medicine, 2021)
Aim: The aim of the study was to explore the perception and practice of physical restraints used by critical care nurses. Design: A qualitative descriptive design was used. Method: From December 2019 to May 2020, a one-to-one, semi-structured in-depth interview with 10 critical care nurses from two intensive care units in a tertiary general hospital with 3,200 beds in China was conducted using the method of purposeful sampling. The data were analyzed using inductive thematic analysis. Findings: The perception of physical restraints among critical care nurses was that patient comfort can be sacrificed for patient safety. Physical restraints protected patient safety by preventing patients from unplanned extubation but influenced patient comfort. Physical restraints were common practice of critical care nurses. Relative physical restraints provided patients with more freedom of movement and rationalization of physical restraints which were the practical strategies. Conclusion: The study identified problems in critical care nurses' perception and practice on physical restraints. Critical care nurses are confident that physical restraints can protect patient safety, and the influence of physical restraints on patient comfort is just like the side effect. Although physical restraints were common practice, critical care nurses still faced dilemmas in the implementation of physical restraints. Relative physical restraints and rationalization of physical restraints help critical care nurses cope with the “bad feelings,” which may also be the cause of unplanned extubation. It is necessary for the adaptation of clinical practice guidelines about physical restraints for critically ill patients in the Chinese context, to change the perception and practice of critical care nurses and deliver safe and high-quality patient care.